2020
DOI: 10.1038/s41598-020-61459-4
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Hypocalcemia as a Risk Factor for Cardiovascular Events and All-Cause Mortality among Patients Undergoing Incident Hemodialysis

Abstract: Lower corrected calcium (cca) levels are associated with a better prognosis among incident dialysis patients. However, cca frequently overestimates ionized calcium (ica) levels. the prognostic importance of the true calcium status defined by iCa remains to be revealed. We conducted a retrospective cohort study of incident hemodialysis patients. We collected data of iCa levels immediately before the first dialysis. We divided patients into three categories: apparent hypocalcemia (low ica; <1.15 mmol/L and low c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 38 publications
1
24
1
Order By: Relevance
“…This was true even for those with normal albumin levels (>38 g/L) where albumin‐adjustment was not required in the Dialysis Outcomes and Practice Pattern Study 28 . Recent literature has suggested that hidden hypocalcaemia (that is low ionized calcium, with normal albumin‐adjusted calcium) poses more significant risk than apparent hypocalcaemia (low ionized calcium with low albumin‐adjusted calcium) with increased risk of all‐cause and cardiovascular disease and events 15,29 . Those with hidden hypocalcaemia were less likely to receive interventions to correct hypocalcaemia, increase doses of vitamin D analogues or calcium, and presumably were less likely to have increased monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…This was true even for those with normal albumin levels (>38 g/L) where albumin‐adjustment was not required in the Dialysis Outcomes and Practice Pattern Study 28 . Recent literature has suggested that hidden hypocalcaemia (that is low ionized calcium, with normal albumin‐adjusted calcium) poses more significant risk than apparent hypocalcaemia (low ionized calcium with low albumin‐adjusted calcium) with increased risk of all‐cause and cardiovascular disease and events 15,29 . Those with hidden hypocalcaemia were less likely to receive interventions to correct hypocalcaemia, increase doses of vitamin D analogues or calcium, and presumably were less likely to have increased monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…So, Yamaguchi suggested the importance of measuring ionized calcium. 29 Hyperuricemia is an independent risk factor for cardiovascular disease. 30 This abnormality in uric acid metabolism increases with the worsening of CKD.…”
Section: Discussionmentioning
confidence: 99%
“… 61 , 62 , 63 Hypocalcemia and low vitamin D (both 25-hydroxy vitamin D and 1,25-dihydroxy vitamin D) concentrations have been associated with increased risk of CVD. 64 , 65 Inhibition of calcitriol (1,25-dihydroxyvitamin D) production due to increased FGF23 66 , 67 is associated with increased cardiac contractility, 68 coronary artery calcification, 69 myocardial fibrosis, 70 and proinflammatory effect. 71 PTH increases the production of calcitriol (1,25-dihydroxyvitamin D), as well as increases bone resorption, which leads to increasing both serum calcium and phosphate concentrations.…”
Section: Ckd-mbd Is a Significant Risk Factor For CV Mortalitymentioning
confidence: 99%